Neurological, neurobehavioral, and radiological alterations in patients with mucopolysaccharidosis III (Sanfilippo's syndrome) in Brazil - Valle, Daniel Almeida do; Santos, Mara Lúcia Schmitz Ferreira; Telles, Bruno Augusto; Cordeiro, Mara L. (Frontiers in Neurology, 2022)
Mucopolysaccharidosis type III (MPS III) or Sanfilippo syndrome is the most common form of MPS, in which neurological involvement in all stages of the disease is prominent. The current study aimed to comprehensively describe the neurological profile of children and adolescents with MPS III who visited the largest pediatric hospital in South America. A prospective/retrospective cohort analysis was performed on 10 patients with MPS III from eight unrelated families. Most patients <12 months of age had achieved development milestones within the expected range for their age, with delay in walking independently and first single word acquisition. Behavioral symptoms were reported in seven patients. Eight patients (80%) developed profound intellectual disabilities. Six patients (60%) had epilepsy, among whom 75% had their first seizure between 2 and 4 years of age; the frequency of which increased with age. Monotherapy was effective in 60% of patients. Two patients, both aged <8 years, had normal baseline electroencephalographic activity. Epileptiform activity was observed in three patients. Cortical atrophy was visualized using magnetic resonance imaging in 71% patients; all but one of these patients were aged >6 years. Neurological abnormalities increased in prevalence and severity with age. Anti-seizure drug resistance was uncommon. Dysmorphological and systemic manifestations were uncommon and mild and did not correlate with neurological involvement. Despite high allelic heterogeneity, neurodegeneration was similar among all patients. Overall, these data contribute to the scarce literature from developing countries.